Leveraging Proptech Management for Improved Organizational Performance in the Property Sector - Dadet Sugiarto; Selamet Riyadi; Jemmy Jemmy; Eryco Muhdaliha; Ravindra Safitra Hidayat (Maneggio, 2025)
The development of technology has brought significant changes in the property sector, especially through the application of Property Technology (Proptech) in business management. This study aims to analyze the effect of Proptech management on improving organizational performance in the property sector. Using a quantitative approach, data is collected through surveys to property companies that have adopted digital technology in their operations. Regression analysis was used to examine the relationship between the application of Proptech with operational efficiency, profitability, and customer satisfaction. The results showed that Proptech management contributes positively and significantly to improving organizational performance. Digitization of management systems, automation of services, and the use of big data analytics proved to be able to improve the efficiency and competitiveness of the company. In addition, the study identifies factors that moderate the effectiveness of Proptech implementation, such as market conditions, government regulation, and organizational readiness to adopt technology. The findings suggest that companies with higher rates of technology adoption tend to have a greater competitive advantage compared to those still implementing conventional systems. The study also revealed that the main barriers to implementing Proptech include high investment costs, digital infrastructure limitations, and resistance to change on the part of internal companies. Therefore, this study provides recommendations for property companies to develop a comprehensive digital transformation strategy to improve management effectiveness and competitiveness in the industry.